2023
DOI: 10.1136/bmjopen-2023-075767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-dose esketamine on postoperative depressive symptoms in patients with breast cancer (EASE): study protocol for a randomised controlled trial

Qingfeng Wei,
Cen Chen,
Jiajia Zhu
et al.

Abstract: IntroductionDepressive symptoms have surfaced as the principal mental health concern among patients with breast cancer, with surgical interventions potentially exacerbating these symptoms and adversely influencing clinical outcomes. This study protocol is designed to investigate the efficacy of low-dose esketamine administered perioperatively on depressive symptoms in patients with breast cancer. It also aims to illuminate the potential neurobiological underpinnings of this effect.Methods and analysisThis rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies have shown that esketamine is associated with a lower rate of adverse reactions than ketamine and demonstrates strong potential to assist anesthesia (Wang et al, 2019). Low-dose esketamine is defined as a dosage of esketamine less than or equal to 0.25 mg/kg (Wei et al, 2023). Previous studies have shown that low-dose esketamine has sympathomimetic effects (Timm et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that esketamine is associated with a lower rate of adverse reactions than ketamine and demonstrates strong potential to assist anesthesia (Wang et al, 2019). Low-dose esketamine is defined as a dosage of esketamine less than or equal to 0.25 mg/kg (Wei et al, 2023). Previous studies have shown that low-dose esketamine has sympathomimetic effects (Timm et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“… 2 Depressive symptoms have become a significant mental health issue among patients with breast cancer, and have become a crucial concern in both clinical practice and public health. 3 Patients with breast cancer are at a higher risk of developing depressive symptoms following diagnosis and treatment compared with patients with non-breast cancer, and there may be some biological link between major depressive disorder and breast cancer. 4 5 A systematic evaluation and meta-analysis of studies on the prevalence of depression in patients with breast cancer worldwide revealed a global prevalence rate of 32.2%.…”
Section: Introductionmentioning
confidence: 99%